2015
DOI: 10.1108/ec-06-2014-0125
|View full text |Cite
|
Sign up to set email alerts
|

CFD investigation of inlet pressure effects on the energy separation in a vortex tube with convergent nozzles

Abstract: Purpose – The purpose of this paper is to investigate the effect of convergent nozzles on the thermal separation inside a vortex tube, using a three-dimensional (3D) computational fluid dynamics (CFD) model as predicting tool. Design/methodology/approach – The 3D finite volume formulation with the standard k-ε turbulence model has been used to carry out all the computations. Six different nozzles for convergence angle have been utilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Various methods are available to determine the Backflow temperature which can be found in the references. In this numerical study, the results of previous references in this field have been used to calculate the Backflow temperature [21,22]. On this basis, the Backflow temperature is assumed to be the mean total temperature of the flow leaving the cold exit.…”
Section: Cold Exitmentioning
confidence: 99%
See 1 more Smart Citation
“…Various methods are available to determine the Backflow temperature which can be found in the references. In this numerical study, the results of previous references in this field have been used to calculate the Backflow temperature [21,22]. On this basis, the Backflow temperature is assumed to be the mean total temperature of the flow leaving the cold exit.…”
Section: Cold Exitmentioning
confidence: 99%
“…They showed that increase in inlet pressure increases the efficiency of vortex tube, but from 6 bars, increase in inlet pressure decreases the efficiency. Zhidkov et al [19], Skye et al [20] and Pourmahmoud et al [21] concluded that increase in pressure increases T ic .…”
Section: Introductionmentioning
confidence: 99%
“…Pourmahmoud et al [21] investigated secondary vortex chamber effect on the cooling capacity enhancement of vortex tube. Also Pourmahmoud et al [22] investigated numerically the inlet pressure effects on the energy separation in a vortex tube with convergent nozzles and one vortex chamber. Lorenzini and Spiga [23] studied the flow field inside vortex tube.…”
Section: Figure 1 Schematic Drawing Of a Vortex Tubementioning
confidence: 99%